Unusual chlorine partitioning in the 2015/16 Arctic winter lowermost stratosphere: observations and simulations - S. Johansson; M. L. Santee; J.-U. Grooß; M. Höpfner; M. Braun; F. Friedl-Vallon; F. Khosrawi; O. Kirner; E. Kretschmer; H. Oelhaf; J. Orphal; B.-M. Sinnhuber; et al. (Atmospheric Chemistry and Physics, 2019)
The Arctic winter 2015/16 was characterized by cold stratospheric temperatures. Here we present a comprehensive view of the temporal evolution of chlorine in the lowermost stratosphere over the course of the studied winter. We utilize two-dimensional vertical cross sections of ozone ( O 3 ) and chlorine nitrate ( ClONO 2 ), measured by the airborne limb imager GLORIA (Gimballed Limb Observer for Radiance Imaging of the Atmosphere) during the POLSTRACC/GW-LCYCLE II/GWEX/SALSA campaigns, to investigate the tropopause region in detail. Observations from three long-distance flights in January, February, and March 2016 are discussed. ClONO 2 volume mixing ratios up to 1100 pptv were measured at 380 K potential temperature in mesoscale structures. Similar mesoscale structures are also visible in O 3 measurements. Both trace gas measurements are applied to evaluate simulation results from the chemistry transport model CLaMS (Chemical Lagrangian Model of the Stratosphere) and the chemistry–climate model EMAC (ECHAM5/MESSy Atmospheric Chemistry). These comparisons show agreement within the expected performance of these models. Satellite measurements from Aura/MLS (Microwave Limb Sounder) and SCISAT/ACE-FTS (Atmospheric Chemistry Experiment – Fourier Transform Spectrometer) provide an overview over the whole winter and information about the stratospheric situation above the flight altitude. Time series of these satellite measurements reveal unusually low hydrochloric acid (HCl) and ClONO 2 at 380 K from the beginning of January to the end of February 2016, while chlorine monoxide (ClO) is strongly enhanced. In March 2016, unusually rapid chlorine deactivation into HCl is observed instead of deactivation into ClONO 2 , the more typical pathway for deactivation in the Arctic. Chlorine deactivation observed in the satellite time series is well reproduced by CLaMS. Sensitivity simulations with CLaMS demonstrate the influence of low abundances of O 3 and reactive nitrogen ( NO y ) due to ozone depletion and sedimentation of NO ...